Assesment of Delivery Platforms and Online Pedagogy Requirements - Ali, Maaruf; Miraz, Mahdi H. (2020 International Conference on Computing, Electronics & Communications Engineering (iCCECE), 2020)
The problem of delivering lectures remotely is not new. It was first done using radio, television and then satellite broadcasting. This paper covers remote learning and the technical requirements of delivering modern online lectures using the Internet. The popular platforms such as Google Meet and Zoom are discussed. The digital divide including broadband availability and affordability are also discussed, covering factors to deployment. The psychological factors affecting online learning are focused upon. It is concluded that a fast, stable internet connection is critical and that, Google Meet offers the best platform. The online material also needs to be delivered in short focussed multimedia rich segments, of a maximum duration not exceeding 2.5 minutes.